Droplet-on-hydrogel bilayer based assay for functional study of membrane proteins - Cocul’ová, Z (2022)
Functional study of membrane proteins, especially when a transmembrane potential is required for protein function, is notoriously difficult. In this thesis, I introduce an experimental assay that adapts the droplet-on-hydrogel technique for a high-resolution functional study of membrane proteins with independent control of the electrical and chemical transmembrane potential.